Pengembangan Sistem Supply Chain Management Usaha Mikro Kecil dan Menengah (UMKM) di Bali (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
This study aims to develop a supply chain management system, reduce events such as stock accumulation and loss of stock at Besek Bali warehouses. This research is also able to help all SMEs who still calculate everything conventionally to use a supply chain management system. The types of data in this study are quantitative and qualitative data types because they are written data regarding the stock of goods from November to December 2021 from Besek Bali in the form of numbers and the results of interviews with the owner of Besek Bali. The method of collecting data is through the observation method in which data from Besek Bali and interviews will be observed. Research testing is done by observing the data obtained from Besek Bali and the results of interviews with the owner of Besek Bali. After the data is observed to determine the factors causing delays and stock accumulation, a supply chain management system will be made using the prototype method. The system was implemented to help reduce delays and stock accumulation as well as reduce loss of stock in the warehouse